Predictors of technique failure and mortality on peritoneal dialysis: An analysis of New Zealand peritoneal dialysis registry data. Issue 6 (29th November 2020) - Hayat, Ashik; Saweirs, Walaa
Abstract: Aim: Technique failure is a major disadvantage associated with peritoneal dialysis (PD). This study aimed to analyse the demographic and risk predictors of technique failure and mortality in patients on PD. Methods: All incidental PD patients registered on the New Zealand Peritoneal dialysis registry (NZPDR) from January 1995 to December 2014 were included in the study. The primary outcomes were time to technique failure and its specific causes, while as the secondary outcome was time to death. Risk predictors of technique failure and mortality were analysed using multivariate Cox proportional hazards (PH) regression model. Besides, competitive risk regression analysis was undertaken to analyse the effect of death as a competing event to technique failure. Results: Of 6379 patients, there were 2993 (46.9%) episodes of technique failure and 2684 (42%) deaths. The crude technique failure and mortality rates were 165 ± 5.90 and 147.9 ± 5.50 (mean ± SD)/1000 patient‐years, respectively. Hazards of technique failure were lower in older individuals above 60 years, HR 0.72 (95% CI 0.67‐0.79), larger centres, HR 0.89 (95% CI 0.79‐1.00) and higher with coiled catheters, HR 1.26 (95% CI 1.16‐1.37). Early nephrology referral, continuous ambulatory peritoneal dialysis (CAPD) and Asian ethnicities were associated with better technique survival. Infections were the major cause of technique failure (58.4%) with peritonitis being the leading cause (30.2%). Conclusion: There are multiple factors associated with risk of technique failure, therefore it is persuasive to construct a mathematical model for early prediction, for a planned transition to HD. SUMMARY AT A GLANCE: Among over 6, 000 PD patients from the New Zealand Peritoneal Dialysis Registry, multiple factors are associated with the risk of technique failure, and the authors call for the construction of a mathematical model for early prediction so that a planned transition to HD can be initiated in a timely manner.